(untitled) (Cardiovascular Journal, 2014)
Background: Acute lower extremity ischemia is a common vascular disease and considered limb- and life- threatening. The present study evaluated and compared the outcome of early and late surgical intervention in acute lower limb ischemia due to thromboembolism. Methodology: This non randomized comparative parallel study was conducted at the Department of Cardiovascular Surgery, NICVD, Dhaka, Bangladesh from January 2007 to December 2008 for duration of two year. Total 80 patients were enrolled in this study. The patients were divided into equal two groups, Group A, for early surgical intervention (with in 24 hours) and Group B, late surgical intervention (more than 24 hours). Results: Mean (±SD) age of both Group A and Group B was 51.93 (±11.73) and 47.00 (± 11.01) years. Male and female ratio of the total study population was 1.76:1 Pain and absence of pulse distal to occlusion was common for all. Cold extremity, sensory deficit, motor deficit, diminish vascular flow was the commonest findings of both group. In Group A, 57.5% had superficial femoral artery occlusion, 22.5% had iliac artery and 20.0% popliteal artery occlusion. In Group B, 42.5% had superficial femoral artery occlusion, 32.5% had popliteal artery occlusion and 25.0% had iliac artery occlusion. Fasciotomy was performed in 15.0% patients of Group A and in 22.0% patients of Group B. After Fogarty embolectomy in group A and group B had warm extremity (80.0% vs. 65.0%), pulsation distal to occlusion (90.0% vs. 75.0%), intact sensory function (82.5% vs. 67.5%), intact motor function (80.0% vs. 65.0%), and normal vascular flow by Doppler US (80.0% vs. 65.0%). During postoperative period history of bleeding, infection, reperfusion injury, muscle necrosis and limb amputation were 12.5% vs. 10.0%, 5.0% and 7.5%, 17.5% vs. 35.0%, 15.0% vs. 12.5% and 37.5% vs. 32.5% respectively. Conclusion: Duration of embolism may be the significant factor determining the outcomes of the management of acute arterial embolism in the lower extremities. The 24- hour duration of arterial embolism is a crucial factor influencing the surgical the management and early diagnosis and shifting of patients to specified centre as early as possible to save limb as well as life. DOI: http://dx.doi.org/10.3329/cardio.v7i1.20799 Cardiovasc. j. 2014; 7(1): 38-43